2013
DOI: 10.1097/mph.0b013e31828d5b3e
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mannitol Hypersensitivity

Abstract: Mannitol is used for increased intracranial pressure and prevention of nephrotoxicity. We present a case report of a patient who experienced an anaphylactic response to mannitol and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In addition, a study in spontaneously hypertensive rats indicated mannitol activates cardiac and renal cell death implicating heart and renal damage (72). Furthermore, clinical studies have strongly emphasized the adverse effects of mannitol in diabetic patients including nephrotoxicity (39) and acute renal failure (12,59,66), as well as anaphylactic reactions under certain pathological conditions (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study in spontaneously hypertensive rats indicated mannitol activates cardiac and renal cell death implicating heart and renal damage (72). Furthermore, clinical studies have strongly emphasized the adverse effects of mannitol in diabetic patients including nephrotoxicity (39) and acute renal failure (12,59,66), as well as anaphylactic reactions under certain pathological conditions (37).…”
Section: Discussionmentioning
confidence: 99%
“…After the infusion was stopped, there was an immediate clinical improvement. The patient was given hydrocortisone, hydroxyzine, and ranitidine without further incident [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in the 1960s suggest that hyperosmolar stimulation can lead to mannitol sensitivity in patients as opposed to an allergic response [ 10 ]. If leukocytes are placed under the right in vitro conditions, basophils can release histamine independent of IgE [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, it is a low molecular-weight, inert hapten. Current guidelines for interpretation of drug allergy testing 10 indicate that positive intradermal and skin-prick tests to mannitol would favour an IgE-mediated mechanism underlying clinical anaphylaxis in both cases. The potential sources of immune sensitisation to mannitol are intriguing; previous mannitol exposure in medications, or other products like mouthwash, chewing gums and processed foods, are possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients had a history of intolerance to mushrooms and avoidance of mannitol in parenteral solutions may have prevented the intraoperative anaphylaxis. There are published reports documenting hypersensitivity reactions to mannitol infusion 10,12,13 . After a thorough literature search, we found only one case reporting anaphylaxis to mannitol where it was used as an excipient in a cisapride tablet 11 .…”
Section: Discussionmentioning
confidence: 99%